Efecto de la inoculación de cuatro bacterias promotoras del crecimiento vegetal sobre parámetros biométricos aéreos de plántulas de QUERCUS ILEX SSP.BALLOTA B. (III Congreso Forestal Español Congreso, 2001)
In the present work has studied the effect of four plant growth-promoting rhizobacteria (PGPRs) on growth of holm-oak plants (Quercus ilex ssp. ballota) in nursery before transplanting. The four strains assayed show in vitro metabolic capacities related with their action PGPR. All strains were able to increase significantly some parameters studied (high, diameter neck and dry weight). However, in the first sampling time (T1) only the strains Aur 6 and Aur 9 increased the high of the plants. In the last sampling time (T3) all strains increased the high, only Aur 6 increased the diameter neck and Cell 3, Aur 6 and Aur 9 increased the dry weight. It is important to point out that Aur 6 and Aur 9 increased the high and also the dry weight, this show that these strains enhance the general metabolism of the plants and also enhance the nutritional capacity and as a result the plants are more robust and with a better adaptative capacity.